Development of biology teaching modules based on the RANDAI learning model to improve students creative thinking and collaboration skills - Lenty Supriwardi; Fitri Arsih; Irdawati Irdawati; Suci Fajrina (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
In the 21st century, students are expected to have 4C skills: critical thinking, creative thinking, collaboration, and communication. Culturally integrated learning has been implemented in learning. Based on the results of observations that have been made, teachers have not implemented a culturally integrated learning model so that learning is not enjoyable and meaningful. This research is a development research. The aim is to determine the level of validity, practicality, and effectiveness of the biology teaching module based on the RANDAI learning model in improving students' creative thinking and collaboration skills. The research subjects were 74 phase F students at SMAN 9 Padang. The biology teaching module development model is the Plomp model which consists of preliminary research phase, development or prototyping phase, and an assessment phase. The research instrument was a closed questionnaire for collaboration and essay questions for creative thinking. The results showed that the validity test had an average of 92.9% with very valid criteria. The results of the practicality test were 86.11% by teachers and 88.62% by students with very practical criteria. The results of the effectiveness test showed the influence of the biology teaching module based on the RANDAI learning model on students' creative thinking and collaboration skills. The conclusion of the RANDAI-based biology teaching module on the respiratory system can provide contextual learning for students and cultural values that can be integrated into learning. These findings confirm that learning integration rooted in cultural context strengthens social and communication skills, fosters empathy and motivation among students, and supports 21st century collaborative competencies.Abstrak. Di abad 21 peserta didik diharapkan memiliki keterampilan 4C yaitu critical thingking, creative thingking, collaboration, dan communication. Pembelajaran yang terintegrasi budaya telah dilaksanakan dalam pembelajaran. Berdasarkan hasil observasi yang telah dilakukan, guru belum menerapkan model pembelajaran yang terintegrasi dengan budaya sehingga pembelajaran belum  menyenangkan dan bermakna. Penelitian ini merupakan penelitian pengembangan. Tujuan adalah untuk mengetahui tingkat kevalidan, kepraktisan, dan keefektivan modul ajar biologi berbasis model pembelajaran RANDAI dalam meningkatkan keterampilan berpikir kreatif dan berkolaborasi peserta didik. Subjek penelitian adalah 74 peserta didik fase F di SMAN 9 Padang. Model pengembangan modul ajar biologi adalah model Plomp yang terdiri dari preliminary research phase, development or prototyping phase, dan assesment phase. Instrumen penelitian adalah angket tertutup untuk keterampilan berkolaborasi dan soal dalam bentuk esai untuk keterampilan berpikir kreatif. Hasil penelitian uji validitas memiliki rata-rata 92,9% dengan kriteria sangat valid. Hasil Uji praktikalitas sebesar 86,11% oleh guru dan 88,62% oleh peserta didik dengan kriteria sangat praktis. Hasil uji efektivitas menunjukkan adanya pengaruh modul ajar biologi berbasis model pembelajaran RANDAI terhadap keterampilan berpikir kreatif dan keterampilan berkolaborasi peserta didik. Kesimpulan modul ajar biologi berbasis model pembelajaran RANDAI pada materi sistem respirasi dapat memberikan pembelajaran kontekstual bagi peserta didik dan nilai-nilai budaya yang bisa diintegrasikan ke dalam pembelajaran. Temuan ini menegaskan bahwa integrasi pembelajaran yang berakar dari konteks budaya memperkuat keterampilan sosial, komunikasi, menumbuhkan empati dan motivasi peserta didik yang mendukung kompetensi kolaboratif abad 21.